2009
DOI: 10.1177/1062860609334898
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Quality Improvement in Academic Medical Centers: A Changing Landscape

Abstract: Efforts to improve the quality of ambulatory care have received tremendous attention as bold new initiatives aimed at influencing the environment of care through financial incentives, public transparency, and information technology rapidly spread. Academic medical centers, which represent a long tradition of excellence and innovation in medical care, might be expected to lead the charge in these new arenas, but motivation for change may be mitigated by the unique complexity and multiple goals of these institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…As noted earlier, practices that were larger, more sophisticated in their administrative infrastructures, and more advanced in having EHR systems were more likely to participate than other practices. This result is consistent with studies that have found that PQRS and quality reporting efforts are generally more practical when a more substantial administrative infrastructure is available (Halladay et al, 2009;Leas, Goldfarb, Browne, Keroack, & Nash, 2009), including EHR (Berman et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…As noted earlier, practices that were larger, more sophisticated in their administrative infrastructures, and more advanced in having EHR systems were more likely to participate than other practices. This result is consistent with studies that have found that PQRS and quality reporting efforts are generally more practical when a more substantial administrative infrastructure is available (Halladay et al, 2009;Leas, Goldfarb, Browne, Keroack, & Nash, 2009), including EHR (Berman et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…Improving ambulatory care poses unique challenges. 18 Despite the fact that there are currently 900 million outpatient visits annually in the United States, compared to 35 million hospital discharges, 19 there has been less effort directed toward improving the quality of outpatient care.…”
Section: Managing High-risk and High-opportunity Areasmentioning
confidence: 99%
“…The authors found EMRs becoming increasingly more common in outpatient settings and may provide the motivation to improve ambulatory, outpatient quality improvement and safety. 4 A systematic review conducted in 2006 by Chaudhry and associates evaluated four benchmark institutions and found HIT to improve quality and efficiency in the delivery of healthcare. 5 Other recommendations for the use of HIT are included in the report by The Institute of Medicine (IOM) emphasizing health care should be supported by systems that carefully produce safe, effective, patient-centered, timely, efficient, and equitable care.…”
Section: Discussionmentioning
confidence: 99%